Advanced educational psychology - Mangal, S.K. (New Delhi : PHI Learning Private Limited, 2022)
Educational psychology is the study of how humans learn in educational settings, the effectiveness of educational interventions, the psychology of teaching, and the social psychology of schools as organizations. It is concerned with how students learn and develop, often focusing on subgroups such as gifted children and those subject to specific disabilities.
Includes bibliographical references and index.
Keywords: Education; Psychology